AN AYURVEDIC MULTIMODULAR TREATMENT OF ALOPECIA TOTALIS (KHALITYA) W.R.T PANCHAKARMA: A CASE REPORT - Aosemba Jamir,; Latika,; Jitender Gauttam,; Prasanth D,; Santosh Kumar Bhatted, (International Journal of Ayurveda and Pharma Research, 2019)
Alopecia areata is characterized by circumscribed non-scarring loss of hair in single or multiple patches over the scalp or body hair. Histopathology shows perifollicular and intrafollicular inflammatory cells infiltrate composed mainly of lymphocytes, described as swarm of bees’ appearance. The characteristic lesion is an asymptomatic, smooth bald patch with normal skin within the patch. Fine regular pitting of nails and tachynochia is a common association. When the hair loss involves the entire scalp it is known as alopecia totalis. Khalitya in Ayurveda is a disease in which Pitta combining with Vata and getting into the pores of hairs (hair follicles) cause fall of hair, and then Kapha along with Rakta obstructs the pores of those hairs and makes it impossible for other hair to grow. As it does not destroy the hair follicles the potential for the re-growth is maintained for many years. However growth in alopecia totalis and universalis is limited. Material and Methods: The present clinical study is a case report on the efficacy of Shamana (pacification) medication along with Vamana (therapeutic emesis), Virechana (therapeutic purgation), Basti (therapeutic Enema) and Nasya (therapeutic nasal medication) and Raktamokshan (therapeutic bloodletting) in the management of a patient diagnosed as Alopecia totalis. Results: There was significant re-growth of the hair of the scalp. SALT Score improved from 97.76 to 2. Discussion: The collected data from this study suggests that Ayurvedic Shodhana (Purification) treatment along with Shamana medications can provide an efficient result for managing Alopecia totalis.